Tuning the biomimetic performances of 4-hydroxyproline-containing cyclic peptoids. Issue 36 (5th September 2018) - Schettini, R.; Costabile, C.; Della Sala, G.; Buirey, J.; Tosolini, M.; Tecilla, P.; Vaccaro, M. C.; Bruno, I.; De Riccardis, F.; Izzo, I.
Abstract : Five new cyclic peptoids containing (2 S, 4 R )-4-hydroxyproline (Hyp) residues have been designed and synthesized using a mixed "submonomer/monomer" approach. Abstract : Five new cyclic peptoids containing (2 S, 4 R )-4-hydroxyproline (Hyp) residues have been designed and synthesized using a mixed "submonomer/monomer" approach. Alkali metal cation affinities and ion transport activities were assessed by experimental (NMR and HPTS assay in liposomes) and computational methods. Easy functionalization of hydroxyproline residues afforded a bouquet of cyclic oligomers showing correlation between ion transport abilities and cytotoxic activities on selected human cancer cell lines.